May family routines impact oral health in American children? - Pardi, Vanessa; Castilho, Giovanna Torqueto; Stewart, Rachel; Luo, Huabin; Wright, Wanda G.; Moss, Mark Eric (Frontiers in Oral Health, 2024)
ObjectivesThe present study aimed to assess the association between family routines and dental caries and self-rated oral health status.MethodsData from the 2020–2021 National Survey of Children's Health (NSCH) completed at United States were used. Our outcome variables were self-reported dental caries (yes/no) and poor oral health condition (yes/no). Our independent variables were related to family routines: (1) Going to bed at the same time (yes/no); (2) Days having dinner together (0–7days); (3) Hours spent in front of the TV, computer, cell phone or other electronic devices (screen time); and (4) adequate sleep (yes/no). We used socioeconomic factors, health insurance coverage, family structure and neighborhood characteristics as covariates. Univariate and multiple logistic regression were used to analyze the data.ResultsFor the dental caries outcome, children with regular bedtimes (AOR = 0.68, 95% CI: 0.58–0.79), more frequent family dinners (AOR = 0.90, 95% CI: 0.85–0.96), and supportive neighborhoods (AOR = 0.88, 95% CI: 0.78–0.99) were less likely to report dental caries. Increased screen time (AOR = 1.10, 95% CI: 1.04–1.15) was associated with higher self-reported dental caries. For oral health status, children with regular bedtimes, (AOR = 0.60, 95% CI: 0.48–0.75), supportive neighborhoods (AOR = 0.81, 95% CI: 0.68–0.97), and with more neighborhood amenities (AOR = 0.92, 95% CI: 0.88–1.00) reported better health. More screen time (AOR = 1.11, 95% CI: 1.02–1.21) and poor neighborhood conditions (AOR = 1.13, 95% CI: 1.02–1.26) correlated with poor oral health.ConclusionsFindings from this study indicate that family routines play a significant role in children's oral health. Future research should focus on interdisciplinary family- and community-level interventions that are tailored to support healthy habits and address the needs of families.